Gastrointestinal Dependent Stromal Tumor of the Small Intestine (Ileum): Case Report and Literature Review - Gonzalez-Dominguez, Francie Dayanera; Ramírez-Vázquez, Jose Luis; Rodriguez-Trejo, Manuel Jose; Betanzos- Planell, Antonio Carlos; Feregrino-Torres, Abraham; Dominguez-Jimenez , Melissa (British Journal of Healthcare and Medical Research, 2023)
Introduction: The cells of Gastrointestinal Tumors show characteristics similar to those of the interstitial cells of Cajal, which play a neuromotor role in the regulation of normal intestinal motility. Clinical case: A 57-year-old female patient came to our service for abdominal pain accompanied by abdominal pain in the hypogastrium for 3 months. The pathological anatomy reports a tumor measuring 4 cm by 3 cm by 2 cm, 20 cm from the ileocecal valve. With a spindle cell pattern, in the immunohistochemical study it presents c-kit (+) and CD 34 (+), with a mitosis index < 5 per 50 field, it is considered low risk. He was referred to the medical oncology service, which decided on adjuvant treatment with imatinib mesylate. Discussion: GISTs are usually incidental findings diagnosed during other operations. These are mostly operations due to malignancies of other dignities.Conclusions: Patients with GIST showed a surprising frequency of coincidences with other benign or malignant tumors.